Answer: 
<u>Step-by-step explanation:</u>

Suppose in 1992 Chris was x years old, his brother was then 2x years old.
6 years later in 1998, Chris is (x+6) years old, his brother is (2x+6),
(x+6)=(2/3)(2x+6)
x+6=(4/3)x+4
(4/3)x-x=6-4
(1/3)x=3
x=6
in 1992, Chris was 6, so in 2018 he will be 6+(2018-1992)=32 years old.
Hello!
We could write this equation as shown below.
5x+7=23
As you can see, your answer will be D) 5x+7=23
I hope this helps!
<h3>
1)</h3>
• 6x -2(x -5) = -2 . . . . given
• 6x -2x +10 = -2 . . . . X Cameron errored here. When multiplying -2 by -5, the result is 10, not -10.
• 4x +10 = -2 . . . . . . x terms are correctly collected
• 4x +10 -10 = -2 -10 . . . . add the opposite of the constant on the left
• 4x/4 = -12/4 . . . . divide by the x-coefficient
• x = -3 . . . . . . . . . . simplify
<h3>2)</h3>
• 11x -10 = -34 . . . . combine like terms
• 11x -10 +10 = 34 +10 . . . . addition property of equality
• 11x = 44 . . . . . . . . simplify
• 11x/11 = 44/11 . . . division property of equality
• x = 4 . . . . . . . . . . . simplify